Patients' perspectives on how to improve diabetes care and self-management: qualitative study. Issue 4 (29th April 2020) - Ndjaboue, Ruth; Chipenda Dansokho, Selma; Boudreault, Bianca; Tremblay, Marie-Claude; Dogba, Maman Joyce; Price, Roberta; Delgado, Pascual; McComber, Alex M; Drescher, Olivia; McGavock, Jonathan; Witteman, Holly
Abstract : Objective: People living with diabetes need and deserve high-quality, individualised care. However, providing such care remains a challenge in many countries, including Canada. Patients' expertise, if acknowledged and adequately translated, could help foster patient-centred care. This study aimed to describe Expert Patients' knowledge, wisdom and advice to others with diabetes and to health professionals to improve diabetes self-management and care. Design and methods: We recruited a convenience sample of 21 men and women. Participants were people of diverse backgrounds who are Patient Partners in a national research network (hereafter Expert Patients). We interviewed and video-recorded their knowledge, wisdom and advice for health professionals and for others with diabetes. Three researchers independently analysed videos using inductive framework analysis, identifying themes through discussion and consensus. Expert Patients were involved in all aspects of study design, conduct, analysis and knowledge translation. Results: Acknowledging and accepting the reality of diabetes, receiving support from family and care teams and not letting diabetes control one's life are essential to live well with diabetes. To improve diabetes care, health professionals should understand and acknowledge the impact of diabetes on patients and their families, and communicate with patients openly, respectfully, with empathy and cultural competency. Conclusion: Expert Patients pointed to a number of areas of improvement in diabetes care that may be actionable individually by patients or health professionals, and also collectively through intergroup collaboration. Improving the quality of care in diabetes is crucial for improving health outcomes for people with diabetes.